NLRP3 Inflammasome Contributes to Host Defense Against Talaromyces marneffei Infection - Ma, Haiyan; Chan, Jasper F. W.; Tan, Yen Pei; Kui, Lin; Tsang, Chi-Ching; Pei, Steven L. C.; Lau, Yu-Lung; Woo, Patrick C. Y.; Lee, Pamela P. (Frontiers in Immunology, 2021)
Talaromyce marneffei is an important thermally dimorphic pathogen causing disseminated mycoses in immunocompromised individuals in southeast Asia. Previous study has suggested that NLRP3 inflammasome plays a critical role in antifungal immunity. However, the mechanism underlying the role of NLRP3 inflammasome activation in host defense against T. marneffei remains unclear. We show that T. marneffei yeasts but not conidia induce potent IL-1 production. IL-1response to T. marneffei yeasts is differently regulated in different cell types; T. marneffei yeasts alone are able to induce IL-1 production in human PBMCs and monocytes, whereas LPS priming is essential for IL-1 response to yeasts. We also find that Dectin-1/Syk signaling pathway mediates pro-IL-1 production, and NLRP3-ASC-caspase-1 inflammasome is assembled to trigger the processing of pro-IL-1 into IL-1. In vivo, mice with the deficiency of NLRP3 or caspase-1 exhibit higher mortality rate and fungal load compared to wild-type mice after systemic T. marneffei infection, which results from the diminished recruitment of CD4 T cells into granulomas in knockout mice. Thus, our study first demonstrates that NLRP3 inflammasome contributes to host defense against T. marneffei infection through CD4 T cell recruitment.